Community, Collaboration, and Climate. Issue 5 (28th May 2023) - Hardin, Johanna; Shahriari, Shahriar
Abstract : The Department of Mathematics & Statistics at Pomona College has long worked to create an inclusive and welcoming space for all individuals to study mathematics. Many years ago, our approach to the lack of diversity we saw in our majors was remediation through programming, which sought to ameliorate student deficits. More recently, however, we have taken an anti-deficit approach with focus on changes to the department itself. The programs we have implemented are described below as enhancing community, collaboration, and climate within our department.